Clinical effect of milk vetch injection combined with ACEI or ARB in early diabetic nephropathy treatment: a systematic review and meta-analysis - Xiao-yu ZONG; Jin ZHOU; Dong-qiang ZHANG (Editorial Office of Chinese Journal of Public Health, 2022)
ObjectiveTo systematically review clinical efficacy of milk vetch (Astragalus sinicus L.) injection combined with angiotensin-converting enzyme inhibitors (ACEI) or angiotensin II receptor blocker (ARB) in early diabetic nephropathy treatment. MethodsWe retrieved literatures published at home and abroad up to November 2021 on clinical effect of milk vetch injection combined with ACEI or ARB in the treatment of early diabetic nephropathy through searching EMBASE, PubMed, the Cochrane Central Register of Controlled Trials, Web of Science database, China National Knowledge Infrastructure (CNKI), China Science and Technology Periodical Database (VIP), and Wanfang Data Knowledge Service Platform. The Bias Assessment Tool Version 2.0 was used to evaluate the quality of studies included; meta-analysis was performed using RevMan 5.3 and STATA 12.0 software. ResultsFrom 18 eligible studies finally screened out according to the inclusion and exclusion criteria, totally 2 056 early diabetic nephropathy patients were pooled in the meta analysis and of the patients, 678 had treatment of milk vetch injection combined with ACEI or ARB and 663 had routine treatment of ACEI or ARB. The results of the meta analysis showed that the clinically effective rate of milk vetch injection plus ACEI/ARB treatment was significantly higher than that of ACEI or ARB treatment (odds ratio [OR] = 4.16, 95% confidence interval [95% CI]: 2.05 - 8.42); compared with those with ACEI or ARB treatment, the patients with milk vetch injection plus ACEI/ARB treatment had significantly lower blood urea nitrogen (mean difference [MD] = - 0.73, 95% CI: - 1.30 - - 0.15), urinary albumin excretion rate (standardized mean difference [SMD] = - 1.90, 95% CI: - 2.38 - - 1.42) and serum creatinine (MD = - 6.61, 95% CI : - 11.28 - - 1.94). ConclusionMilk vetch injection combined with ACEI or ARB can improve overall clinical treatment efficacy and reduce urinary albumin excertion ratio, creatinine and urea nitrogen in patients with early diabetic nephropathy.